Vertical distribution of 137Cs in soddy-podzolic sandy soil in grasslands and forests of the Bryansk region in 2015–2016 - V. P. Ramzaev; A. N. Barkovsky; K V. Varfolomeeva (Радиационная гигиена)
Vertical distribution of natural and man-made radionuclides in the soil profile is a decisive parameter when calculating the dose rate of gamma radiation in the air above the ground and the effective dose of external human exposure. The main purpose of this work was to determine vertical distribution of 137Cs in soddy-podzolic sandy and sandy-loam soils in forests and grasslands in the south-western districts of the Bryansk region in the remote period after the Chernobyl accident. In 2015–2016, soil cores were sampled in 7 virgin meadows and 13 forested areas to a depth of 20 cm. The cores were cut into horizontal layers 2 cm thick. The 137Cs activity in the samples was determined using a semiconductor gamma spectrometer. The activity concentration in samples of dry soil (n = 200) ranged from 6.35 Bq/kg to 83300 Bq/kg with an average of 4550 Bq/kg. In the meadows in three cases, the maximum activity concentration was determined in the uppermost layer. With increasing depth, the activity concentration decreased and reached a minimum in the deepest layers. A difference between the surface layer and the deepest layer was two to three orders of magnitude. The three other meadows showed a relatively uniform distribution of 137Cs in the upper 4–6 cm, followed by a decrease in activity concentration with an increase in depth. In one meadow area, a peak of the 137Cs activity was found at a depth of 4–6 cm. In the forest, the most typical (in 10 cases) was the presence of a pronounced maximum activity concentration of 137Cs in the uppermost layer. The experimentally obtained values of the 137Cs inventory in the upper 20 cm of soil at the surveyed sites ranged from 42 to 1940 kBq/m2. The values of 137Cs inventory positively and statistically significantly correlated with officially established levels of 137Cs surface ground contamination for the territory of nearby settlements. Vertical migration of 137Cs in the soil in the surveyed areas was mainly limited to the upper 10 centimeters. The layer on average contained 94% of the total 137Cs inventory. Less than 1% of the total 137Cs inventory was found in the deepest soil layer sampled (18–20 cm). The obtained 137Сs activity distributions were used to calculate kerma rate in the air at a height of 1 m above the ground at the surveyed sites. The air kerma rate ranged from 52 to 2240 nGy/h (on average, 807 nGy/h). The caesium-137 deposit in the upper 6 cm of soil determined about 95% and 90% of the air kerma rate in the forests and in meadows, respectively. Radioactive caesium, which migrated into the soil to a depth of more than 10–12 cm, gave a negligible contribution (less than 1%) to the gamma-radiation dose rate in the air. In practical terms, it indicates that the depth of soil sampling equal to 20 cm is currently quite sufficient to estimate the dose rate of gamma radiation in the air in virgin grasslands and in forests.